Does Having Insurance Beneficial for The Indonesian Fisher’s Welfare? - Pramu Maisandi; Alin Halimatussadiah (Balai Besar Riset Sosial Eonomi Kelautan dan Perikanan, 2023)
Fishing is one of the occupations with a significant risk of occupational accidents, which is compounded by the advent of health problems resulting from the Covid-19 pandemic. Both of these risks can lower fisher’s earnings and affect their welfare. This research aims to examine how insurance ownership affected the degree of welfare among Indonesian fishers during the Covid-19 Pandemic. The author uses two different datasets from the National Socioeconomic Survey (Susenas) and applies the Propensity Score Matching (PSM) approach to address the research questions. The PSM method, one of the quasi-experiments approaches, ensures a causal relationship between the dependent variable and the independent variable. The fisher’s household expenditures serve as a proxy for its revenue, hence the greater the value, the more prosperous the fisher’s household. According to the study’s findings, owning health and occupational accident insurance can raise household expenses for fishers, which indicates that insurance ownership may have an impact on the degree of the well-being of Indonesian fishers. Furthermore, it was discovered by this study that the advantages enjoyed by a fisher in Western Indonesia and Eastern Indonesia differed significantly. Another finding is that the percentage of fishers in Indonesia who were covered by insurance was still relatively low. On the other hand, the value of the benefits that come with insurance ownership in fisher’s households is relatively high. As a result, the best advice that can be provided to the government of Indonesia is to encourage insurance ownership on the part of the fishers.